2019
DOI: 10.1016/j.ebiom.2019.07.053
|View full text |Cite
|
Sign up to set email alerts
|

Novel cell adhesion/migration pathways are predictive markers of HDAC inhibitor resistance in cutaneous T cell lymphoma

Abstract: Background Treatment for Cutaneous T Cell Lymphoma (CTCL) is generally not curative. Therefore, selecting therapy that is effective and tolerable is critical to clinical decision-making. Histone deacetylase inhibitors (HDACi), epigenetic modifier drugs, are commonly used but effective in only ~30% of patients. There are no predictive markers of HDACi response and the CTCL histone acetylation landscape remains unmapped. We sought to identify pre-treatment molecular markers of resistance in CTCL tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 78 publications
0
32
0
2
Order By: Relevance
“…Showe et al [112] first described the loss of STAT4 expression in SS PBMCs, and Litvinov et al [113] confirmed that low STAT4 expression in CTCL lesional skin is associated with progressive disease. However, in a separate study, higher STAT4 expression was associated with HDACi resistance in MF/SS patients [114], suggesting that alternative pathways to malignancy may be active in these patients.…”
Section: Well-established Ss-unique Biomarker Genesmentioning
confidence: 91%
“…Showe et al [112] first described the loss of STAT4 expression in SS PBMCs, and Litvinov et al [113] confirmed that low STAT4 expression in CTCL lesional skin is associated with progressive disease. However, in a separate study, higher STAT4 expression was associated with HDACi resistance in MF/SS patients [114], suggesting that alternative pathways to malignancy may be active in these patients.…”
Section: Well-established Ss-unique Biomarker Genesmentioning
confidence: 91%
“…Precise predictive indicators for therapeutic responses are a recognized unmet need 140 . Downregulated expression of the BCL11B gene 159 , overexpression of LAIR2 160 , or recurrent genetic alterations ( RAD23B copy number loss and STAT3 Y640F variant 161 ) have been reported as potential indicators of HDACi resistance in laboratory investigations. Using the assay for transposase-accessible chromatin sequencing (ATAC-seq) that can map the open chromatin sites throughout the genome, a seminal study indicated that only patients who responded well to HDACis showed a gain of chromatin accessibility in CTCL cells after treatment 162 , 163 .…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…Recently, Andrews et al . [ 48 ] showed differences in the acetylation levels of gene regulatory elements between HDACi-sensitive and HDACi-resistant CTCL patients. These changes were linked to the different expression of genes involved in the cell cycle, apoptosis, cytokine/chemokine signaling, and cell adhesion/migration pathways.…”
Section: Hdaci In Clinical Trialsmentioning
confidence: 99%
“…These changes were linked to the different expression of genes involved in the cell cycle, apoptosis, cytokine/chemokine signaling, and cell adhesion/migration pathways. In HDACi-resistant samples, increased acetylation was particularly significant near potential MF/SS oncogenes CCR6, CXCR4, and LAIR2 [ 48 ]. The last one was suggested to be used as an HDACi-resistant marker.…”
Section: Hdaci In Clinical Trialsmentioning
confidence: 99%